Application towards the Concept of Rechtsvinding and Rechtsschepping by the Judges in Deciding a Case - Harifin A. Tumpa (Hasanuddin Law Review, 2015)
The judge may not refuse to examine and to decide a case which has been submitted to the court despite having unclear or non-existent legal pretext. The judge are expected to be able to explore values and sense of justice that grows and embodies the community as the living law. The concept of justice here is not the outcome by the human intellectualism, but rather from his/her own spirit. A justice could not exist or be born from a mere theory, because justice is naturally born from the deepest conscience of a judge who is also a human being. A person’s conscience can not come in sudden, but was born through the process, practice or habit. Either legal finding (Rechtsvinding) or the creation of law (rechtsschepping) should be used in providing justice for litigants as follows: First, in absence of the relevant rules within the existing legislation. Second, regulated by the law but insufficiently clear and contain multi-interpretations. Third, regulated by the law but no longer meet the public sense of justice (out of date). Fourth, based on a jurisprudence or an expert opinion.